Pengarusutamaan Nilai-nilai Sufisme dalam Pendidikan Islam Indonesia Kontemporer - Rubaidi, Rubaidi (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2020)
This article reexamines and rediscusses the importance of the dimensions of Sufism virtues ​​as the foundational spirit of Indonesian Islamic education today amidst its social dynamics. This article is based on participatory research on psudo-Sufism, namely the Shalawat Adlimiyah located in districts of Bojonegoro and Pasuruan. Findings show that the Sufism dimension is effective in reducing moral decadence and strengthening character education. The teacher-student relationship as the core of Sufism teachings is the entry point as well as a capital for the processes of shaping personality and morality, both of which are the essential in character education. This practice has occurred for hundreds of years in the tradition of Sufism education and is still ongoing today. One of its representations is through Sufism education in the circles of Shalawat Adlimiyah. This paper suggests that mainstreaming Sufism values into the practice of Islamic education is urgently needed in addressing the problems of contemporary Indonesian Islamic education.